Electroosmotic permeability in kaolinite and CaCO3 poultice mixtures - Eslami, Naser; Feijoo, Jorge; Paz-García, Juan M.; Franzoni, Elisa; Ottosen, Lisbeth M. (Journal of Cultural Heritage, 2024)
Electrokinetic treatment of masonry for desalination or electroosmotic dewatering depends on a poultice, in which the electrodes are placed, which fulfills several purposes. Poultice composed of kaolinite and CaCO3 have been shown to have good workability and high pH buffering capacity. In this work, the elec- troosmotic (EO) permeability is studied in different kaolinite - CaCO3 mixtures. In addition, the effect on EO of using NaCl as a mixing solution is investigated. A special cell is used to test the EO in the speci- mens. A phenomenological approach, based on the potential gradient and the flux of solution, was used to calculate the EO flow rate and EO permeability coefficient. Results showed that by increasing the con- centration of CaCO3 in the poultice mixture, the EO flow rate decreased and the poultice with 80 % CaCO3 and more did not have any EO flow. Furthermore, the ionic strength in the mixing solution decreases the EO flow rate.